Wars, Traumas, and Identities in the Serbian Novel 1991–2021 (I) - Brajović, Tihomir D. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
This paper briefly introduces the general attitudes that some of the most prominent Serbian writers formulated about war and trauma, as well as national and supranational self-understanding. In the second part of the paper, on the examples of contemporary novels, the author deals with the “circular-evocative” paradigm as one of the magistral choices in the literary treatment of personal and/or collective war traumas. It is based on repetitive recognition of past events and their meanings in the present situations as a kind of collectively understandable, circular identity pattern.
Keywords: Serbian literature; novel; war; trauma; identity; nation; poetics; paradigm; history; culture